Bivalirudin versus unfractionated heparin for residual thrombus burden: A frequency‐domain optical coherence tomography study. Issue 4 (22nd August 2014) - Vergallo, Rocco; Joye, Russell; Barlis, Peter; Jia, Haibo; Tian, Jinwei; Soeda, Tsunenari; Minami, Yoshiyasu; Hu, Sining; Dauerman, Harold L.; Toma, Catalin; Chan, James; Lee, Hang; et al.
<x xml:space="preserve">Abstract</x> Objectives This study aimed to compare the effect of bivalirudin and unfractionated heparin (UFH) on residual thrombus burden assessed by frequency‐domain optical coherence tomography (FD‐OCT), and on angiographic indices of microvascular obstruction (MVO). Background The efficacy of bivalirudin to inhibit thrombus formation inside the stent during percutaneous coronary interventions (PCI) as compared to UFH is unknown. Methods Sixty patients with coronary artery disease who underwent post‐PCI FD‐OCT were studied, including 20 patients treated with bivalirudin and 40 control patients treated with UFH, matched by clinical presentation, stent characteristics, and periprocedural medications. In‐stent thrombus volume, thrombus score (number of quadrants with thrombus), and thrombus type (white/red) were assessed by FD‐OCT. Thrombolysis in myocardial infarction (TIMI) flow grade, corrected TIMI frame count (cTFC), and Quantitative Blush Evaluator (QuBE) score were recorded. Results Patients treated with bivalirudin showed similar thrombus volume (0.14 mm3 [0.00–0.88] vs. 0.13 mm3 [0.00–0.63], P = 0.962), thrombus score (10 [0–25] vs. 8 [0–21], P = 0.849) and thrombus length (1.70 mm [0.00–4.10] vs. 1.40 mm [0.00–4.05], P = 0.968], as compared with patients treated with UFH. Patients in the bivalirudin group showed lower proportion of white thrombus (55.5% vs. 78.6%, P = 0.016). There was no significant difference in TIMI flow grade, cTFC, and QuBE score between the two groups. Conclusions The present study showed similar residual thrombus burden and angiographic indices of MVO immediately after PCI between patients treated with bivalirudin and those treated with UFH. © 2014 Wiley Periodicals, Inc.